2015
DOI: 10.5194/hess-19-3541-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of beaver dams on hydrologic and temperature regimes in a mountain stream

Abstract: Abstract. Beaver dams affect hydrologic processes, channel complexity, and stream temperature in part by inundating riparian areas, influencing groundwater–surface water interactions, and changing fluvial processes within stream systems. We explored the impacts of beaver dams on hydrologic and temperature regimes at different spatial and temporal scales within a mountain stream in northern Utah over a 3-year period spanning pre- and post-beaver colonization. Using continuous stream discharge, stream temperatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 49 publications
8
62
0
Order By: Relevance
“…The increase in groundwater elevation surrounding beaver ponds likely results in increased flow throughout the summer as water is slowly released2829. We also found that water temperatures stayed the same or decreased throughout reaches with beaver ponds, and that diel fluctuation was dampened.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The increase in groundwater elevation surrounding beaver ponds likely results in increased flow throughout the summer as water is slowly released2829. We also found that water temperatures stayed the same or decreased throughout reaches with beaver ponds, and that diel fluctuation was dampened.…”
Section: Discussionmentioning
confidence: 53%
“…Because dams slow water and often increase the area of solar input, a common assumption is that temperatures increase in impounded reaches30. However, quantitative evidence supporting3132 or refuting33 this claim suggests that the complex interaction of solar input, and exchange with the hyporheic or groundwater call into question this simple generality29. In Bridge Creek, increased residence time and the slowed release of potentially cooler water after the construction of BDAs also increases habitat quantity during times of very low discharge observed during hot summer conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of beavers on water temperature have been studied quite extensively with varying results, but with the common conclusion that beaver damming increases water temperature (Majerova et al. ); at higher temperature, gas solubility decreases. The daily variation in CH 4 ebullition is also related to changes in atmospheric pressure, and bubble fluxes tend to be higher when the pressure is decreasing (Maeck et al.…”
Section: Short‐term Carbon Emissions From Beaver Pondsmentioning
confidence: 99%
“…There is a clear need for more detailed methods that assess the influence of beaver dams on channel hydraulics over different flow ranges as they relate to changes in stream ecosystems. Majerova et al () also highlighted the need for a better understanding of spatial and temporal variability of streamflow and temperature in beaver impacted reaches. They concluded that if beaver dam complexes are to be successfully used as a restoration tool, a better understanding of their influences on stream ecosystems needs to be reached through more quantitative field and modelling studies.…”
Section: Introductionmentioning
confidence: 99%